1986
DOI: 10.1073/pnas.83.14.5015
|View full text |Cite
|
Sign up to set email alerts
|

Expression of proenkephalin messenger RNA by mouse spermatogenic cells.

Abstract: The presence of proenkephalin mRNA in germ cells purified from adult mouse testis was examined using RNA gel-and dot-blot analyses. Both pachytene spermatocytes and round spermatids were shown to contain concentrations of this transcript that are 2-to 3-fold greater than that found for whole mouse testis, on a per ug ofpolyadenylylated RNA basis. spermatocytes, round spermatids, and residual bodies were isolated on linear gradients of bovine serum albumin using a modification (14) of the method of Romrell et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…With regard to EOPs, the genes encoding the opioid precursors PENK, POMC and PDYN were found to be expressed in the rat and mouse testes (38,39,46), supporting the idea that testicular function could be regulated through local synthesis of EOPs. The finding that transgenic mice who overexpress PENK in the testes have impaired fertility, morphologically abnormal testicles and low sperm motility has provided further evidence suggesting that the opioid system participates in an important way in the regulation of testicular function (47).…”
Section: Regulation Of Testicular Function By the Opioid Systemmentioning
confidence: 74%
See 1 more Smart Citation
“…With regard to EOPs, the genes encoding the opioid precursors PENK, POMC and PDYN were found to be expressed in the rat and mouse testes (38,39,46), supporting the idea that testicular function could be regulated through local synthesis of EOPs. The finding that transgenic mice who overexpress PENK in the testes have impaired fertility, morphologically abnormal testicles and low sperm motility has provided further evidence suggesting that the opioid system participates in an important way in the regulation of testicular function (47).…”
Section: Regulation Of Testicular Function By the Opioid Systemmentioning
confidence: 74%
“…In addition, binding studies have revealed the presence of all three types of opioid receptors (DOR, MOR and KOR) in rat testes. Moreover, the genes encoding the opioid precursors PENK, PDYN and POMC have also been found to be expressed in the testes of the rat and mouse (38,39), providing further evidence that the opioid system may play a role in regulating testicular function.…”
Section: Regulation Of Testicular Function By the Opioid Systemmentioning
confidence: 93%
“…Recently, mRNA encoding Metenkephalin precursor, preproenkephalin (ppEnk), has been found not only in the nervous systems but also in various non-neuronal tissues such as lymphocytes [1], heart [2], and reproductive systems [3]. In the testis, spermatogenic germ cells [4,5] and Sertoli cells [6] contain ppEnk mRNA. The size of ppEnk mRNA in the germ cells is 1.7-1.9 kb, which is larger than those found in other tissues (1.45-1.5 kb) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the testis, spermatogenic germ cells [4,5] and Sertoli cells [6] contain ppEnk mRNA. The size of ppEnk mRNA in the germ cells is 1.7-1.9 kb, which is larger than those found in other tissues (1.45-1.5 kb) [4,5]. This specific type of ppEnk mRNA can be translatable into a precursor because Met-enkephalin immunoreactive peptides are generated by limited proteolysis of the The nucleotide sequence presented here has been submitted to the EMBL/GenBank database under the accession no.Y07503 extracts of haploid germ cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although many peptides which are synthesized from precursors through cleavage at basic sites have been reported to be present in the testis, most of them are produced in the somatic cells, such as Leydig and Sertoli cells [18]. One of the candidate substrates is proenkephalin, since its mRNA is detected in fractionated spe~atogenic cell populations [21,22], and since one of its processed products, Met-enkephalin-Arg-Phe, is detectable in the sperm acrosome [22]. However, the distribution of proenkephalin transcript in individual cells within the intact testis Antisense Sense has not been examined.…”
Section: Resultsmentioning
confidence: 99%